An atmospheric chronology for the glacial-deglacial Eastern Equatorial Pacific - Zhao, Ning; Keigwin, Lloyd D. (Nature Communications, 2018)
Paleoclimate reconstructions are only as good as their chronology. In particular, different chronological assumptions for marine sediment cores can lead to different reconstructions of ocean ventilation age and atmosphere-ocean carbon exchange history. Here we build the first high-resolution chronology that is free of the dating uncertainties common in marine sediment records, based on radiocarbon dating twigs found with computed tomography scans in two cores from the Eastern Equatorial Pacific (EEP). With this accurate chronology, we show that the ventilation ages of the EEP thermocline and intermediate waters were similar to today during the Last Glacial Maximum and deglaciation, in contradiction with previous studies. Our results suggest that the glacial respired carbon pool in the EEP was not significantly older than today, and that the deglacial strengthening of the equatorial Pacific carbon source was probably driven by low-latitude processes rather than an increased subsurface supply of upwelled carbon from high-latitude oceans.